Análise das características intervenientes na conformação do ambiente de prática do enfermeiro no espaço hospitalar - Leite, Kamilla Rodrigues (2020)
ABSTRACT: Introduction: Seeking improvements in health care, in order to ensure patient safety and the quality of care provided, requires investing in professional nursing practice by promoting favorable work environments. Analyzing the work environment in which nurses are developing their professional practice should be a priority for nursing managers, and the first step is to verify whether or not there are factors that facilitate or hinder professional practice. In order to address the characteristics that are present in the nurse's practice environment and in understanding its influence for professional practice, the question is: how do nurses assess their practice environment? Do sociodemographic and professional factors influence nurses' perception of their practice environment? Objective: To analyze the nurse's practice environment in the hospital space. Method: A cross-sectional, analytical study, with a quantitative approach, developed in a public hospital under municipal management, maintained by the Unified Health System, in the city of Cuiabá - MT, Brazil. The population accessed consisted of 117 professional nurses, assigned to the hospital, the locus of the research and, in exercise, with the nursing service. Data collection took place in the last semester of 2019, using three instruments, namely: sociodemographic and professional profile; economic classification criteria ABEP (2018) of professionals and the Practice Environment Scale - PES. The collected data were analyzed and described using Statistics / Data Analysis (Stata) version 12. Descriptive statistics were used with the elaboration of tables of absolute (n) and percentage (%) of categorical variables and calculation of position measurement. and dispersion (median, standard deviation, minimum and maximum values) for continuous quantitative variables. For the correlation analysis of the dependent and independent variables, we used the Fisher's Correlation test. The study was approved by the Ethics Committee on Health Research with Human Beings of the Federal University of Mato Grosso - Campus Rondonópolis, under the opinion number 3.432.757. Results: The characterization of the nurses' sociodemographic and professional profile found a predominance of females (82.52%), married / stable partners (45.63%), the average age was 39.58 years and 65.05% nurses declared themselves to be heads of household. The health institution studied was classified as an unfavorable environment for professional practice, obtaining an average of 2.35 of the general PES score. The analyzes revealed that 62.14% of nurses perceived their practice environment as unfavorable, the only dimension perceived for having favorable characteristics was the “collegial relations between nurses and doctors” with 68.93%. The nature of the bond (p <0.004), the increase in working time at the institution (p <0.025) and the type of hospitalization unit that is filled (p <0.044) have a significant relationship with the nurses' perception of the environment professional practice. The largest proportion of nurses noticed a lack of professional recognition on the part of management, limitations in actions for professional development and an insufficient number of nursing staff to provide quality care to patients. Conclusion: Finally, it is concluded that the nurses participating in the research believe they have few favorable characteristics present in the professional practice environment that contribute to their participation in the discussion of hospital issues; little access to the fundamentals of nursing focused on the quality of care; skill, leadership and support from nursing coordinators / supervisors to nurses / nursing staff; lack of adequacy of the team and resources. Recognizing the problem, it is recommended to consider these findings, in order to subsidize the managers of health institutions to the conditions of planning, adequacy of conducts and actions that seek the best working conditions for nurses to develop professional practice, reinforcing the importance of presence of favorable characteristics in the nursing practice environment.